Development of a Portfolio-Based Authentic Assessment Instrument to Measure the Development of Multiple Intelligence in 4-5 Year Old Children - Aisyah, Siti (Generasi, 2025)
Backround: Early childhood assessment practices predominantly focus on linguistic and logical-mathematical abilities, neglecting other intelligence domains and failing to capture the multidimensional nature of children s development. Existing assessment instruments lack integration of authentic portfolio approaches with comprehensive multiple intelligence frameworks for children aged 4-5 years.Objective: This research aimed to develop and validate a comprehensive portfolio-based authentic assessment instrument for measuring multiple intelligence development in children aged 4-5 years, establishing its psychometric properties and practical feasibility.Method: The study employed Research and Development methodology following the ADDIE model with qualitative-dominant mixed-methods approach. Data were collected through needs analysis surveys, expert validation protocols involving nine specialists, and field testing across five early childhood settings with ten educators and 47 children over four months. Analysis utilized thematic analysis, Content Validity Index calculation, reliability coefficients, and inter-rater agreement measures. Findings and Implications: The instrument demonstrated strong validity (CVI=0.89), internal consistency (a=0.82-0.91), and inter-rater reliability (ICC=0.80). Field testing confirmed practical feasibility with educators collecting comprehensive evidence across eight intelligence domains. The rotating observation focus system effectively addressed implementation challenges. Results provide educators with evidence-based tools for holistic assessment, support policy advocacy for authentic assessment practices, and enhance family engagement through meaningful developmental documentation.Conclusion: The validated instrument successfully integrates portfolio-based authentic assessment with multiple intelligence theory, offering practical solutions for comprehensive early childhood assessment while demonstrating feasibility in diverse educational settings.